Représentation sociale du milieu marin et iconographie du territoire chez des élus de communes littorales françaises - Béatrice Le Moel; Pascal Moliner; Thierry Ramadier (VertigO)
In this study, we asked mayors and deputies (n =141) of coastal towns (n =39) spread over 4 French geographical areas (Atlantic Ocean coast, Languedoc-Roussillon, Manche and Provence Alpes Côte d’Azur) to draw a map of their municipality. Participants were asked to perform two verbal association tasks designed to explore their representations of the coastal part of their municipality. The analysis of verbal association (hierarchical clustering analysis and similarity analysis) reveals three types of anchoring for theses representations. Based on these various anchors, we identify three subgroups of elected representatives. The analysis of the drawings contents shows that according to the anchor of their representation of coastal territory, the participants do not produce the same types of drawings. This research validates the hypothesis of a link between social and spatial representations, and their translation into iconography. Ultimately, this research proposes an original methodology to study the social meanings assigned to territories.